Spontaneous and severe haematomas in patients with COVID-19 on low-molecular-weight heparin for paroxysmal atrial fibrillation - Maria Mazzitelli; Francesca Serapide; Bruno Tassone; Domenico Laganà; Enrico Maria Trecarichi; Carlo Torti (Mediterranean Journal of Hematology and Infectious Diseases)
x